Intravenous beta-adrenoblocker therapy in acute coronary syndrome patients - S. N. Tereshchenko; I. V. Zhirov (Кардиоваскулярная терапия и профилактика)
Early treatment optimization improves clinical outcomes and reduces morbidity and mortality in patients with acute myocardial infarction (AMI). Intravenous beta-adrenoblocker (BAB) therapy, associated with improved survival, is well tolerated by AMI patients. The results of relevant clinical trials are presented. The causes of possible increase in cardiogenic shock risk for metoprolol group, COMMIT trial, are analyzed. Evidence base for early BAB therapy in AMI patients is presented.